No longer homeless : how the ex-homeless get and stay off the streets - Wagner, David; Atticks, Gemma, 1981- (Rowman & Littlefield, 2018)
No Longer Homeless is a powerful look at a group of people we rarely hear about-those who have formerly been on the streets-sharing the details of their lives to help individuals, organizations, and communities learn to better support the ongoing challenges of homelessness.